Utilization of Fermented Water Hyacinth (Eichhornia crassipes) Meal Using Cow Rumen Liquor in Diets on Growth of Tambaqui (Colossoma macropomum) Fingerling - Hana Delia Hutabarat; Indra Suharman; Adelina ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted for 56 days from April to May 2017. The aim of this research was to determine the number of water hyacinth meal fermented in fish feed formulation tambaqui (Colossoma macroponum), the effect on growth, feed efficiency and protein retention. This study uses a completely randomized design (CRD) with one factor, five level treatments and three replications. The fish used in this research with size 3-5 cm in 0,4-0,5 g of weight. Fish were reared in 1 m3 in cages with the stocking density of 20/cage. Feeding trials were replacing with soybean meal with water hyacinth fermentation applied to P0 (0%), P1 (10%), P2 (20%), P3 (30%) and P4 (40%) for 35% of protein content. The result showed that fermentation of water hyacinth has significant effect (P<0,05) on growth, feed efficiency and protein retentions. Replacement 30% of water hyacinth fermentation is the best response, produce the highest specific growth rate 5,3%, feed efficiency 90,8%, protein retention 34,85%, digestion respectively 61,69% and survival rate 100%.Key word : Colossoma macropomum, Water hyacinth, Fermentation, Rumen Liquor